Li diffusion in plagioclase crystals and glasses – implications for timescales of geological processes - F. Pohl; H. Behrens; M. Oeser; F. Marxer; R. Dohmen (European Journal of Mineralogy)
The growing interest in Li diffusion as a tool to determine timescales of short-time magmatic events, such as magma ascent during eruption, increases the necessity to better understand Li diffusion in common mineral phases. In this context, well-constrained diffusion coefficients and understanding of kinetic processes specific to mineral phases are of crucial importance. To gain further insight especially into the kinetic processes in plagioclase, we investigated the diffusion of Li between natural An61 plagioclase crystals and synthetic glasses of An80 plagioclase composition. Experiments were conducted at 200 MPa in rapid-heat/rapid-quench cold-seal pressure vessels (RH/RQ CSPVs) and internally heated pressure vessels (IHPVs) at temperatures between 606 and 1114 °C. Concentration and isotope profiles of Li were measured using femtosecond laser ablation multicollector inductively coupled plasma mass spectrometry (fs-LA-MC-ICP-MS). We adopted a multispecies diffusion model and specified boundary conditions for plagioclase of labradoritic composition. Using this model, we were able to distinguish between an interstitial (<msubsup>DLii</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="16pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="30645ff0c4d842e6c659e0750ea32bcd"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-36-985-2024-ie00001.svg" width="16pt" height="17pt" src="ejm-36-985-2024-ie00001.png"/></svg:svg>) and a vacancy process (<msubsup>DLiA</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="16pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="46ec750f593ba86bb4f1eac26d7755eb"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-36-985-2024-ie00002.svg" width="16pt" height="17pt" src="ejm-36-985-2024-ie00002.png"/></svg:svg>), with the interstitial process being 0.2–1 orders of magnitude faster than the vacancy process, depending on temperature.